mobility of phosphorus, iron, and manganese through the sediment–water continuum of a shallow eutrophic freshwater lake under stratified and mixed water-column conditions - Giles, Courtney D; Isles, Peter D. F; Manley, Tom; Xu, Yaoyang; Druschel, Gregory K; Schroth, Andrew W (Biogeochemistry, 2016)
The management of external nutrient inputs to eutrophic systems can be confounded due to a persistent pool of phosphorus (P) in lake sediments. The behaviors of P and trace metals depend largely on the reductive dissolution of amorphous iron (Fe) and manganese (Mn) (oxy)hydroxides in sediments; however, a holistic understanding of these dynamics in relation to the broader ecological and hydrodynamic conditions of the system remains elusive. We used a high-frequency monitoring approach to develop a comprehensive conceptual model of P, Mn, and Fe dynamics across the sediment water continuum of a shallow bay in Lake Champlain (Missisquoi Bay, USA). The greatest release of sediment P, Mn, and Fe occurred under stable hydrodynamic conditions, particularly during the onset of the cyanobacterial bloom and was associated with low available P and the accumulation of soluble Mn and Fe above the sediment–water interface (SWI). During the warmest part of the season, bloom severity and sediment P release was partially regulated by hydrodynamic drivers, which changed on hourly time scales to affect redox conditions at the SWI and bottom water concentrations of soluble P, Mn, and Fe. A geochemically distinct increase in soluble P and Fe concentrations, but not Mn, marked the influence of riverine inputs during a late season storm disturbance. Despite continued depletion of the reactive sediment P and metals pool into the bloom period, declining temperatures and a well-mixed water column resulted in bloom senescence and the return of P, Mn, and Fe to surface sediments. The closed cycling of P and metals in Missisquoi Bay poses a significant challenge for the long-term removal of P from this system. Multiple time-scale measures of physical and biogeochemical changes provide a basis for understanding P and trace metals behavior across sediments and the water column, which shape seasonally variable cyanobacterial blooms in shallow eutrophic systems.